Epidemiology of syphilis in Latvia - Rubins, A... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1999)
Background: The present paper discusses the epidemiology of syphilis and contains characterization of the increase of cases in Latvia. Materials and methods: Epidemiologic, clinical and diagnostic data on cases of syphilis in Latvia have been summarized. Clinical diagnosis of suspected syphilis was confirmed by positive dark field examination or by positive serologic tests for syphylis. Results: In 1993, there were 830 recorded syphilis cases in Latvia, in 1994 the number of cases amounted to 1521, in 1995 to 2357, in 1996to 3124, in 1997 te 3008, in 1998 to 2597. An analysis is given of syphilis patients according to the age and stage of the disease, secondary syphilis being prevalent. Conclusions: It has been shown that the increase in syphilis cases is due to lack of prophylactic educational measures among the population. Comparative figures dating from various years are mentioned.
Keywords: Age factors; Epidemiology; Incidence; Latvia; Syphilis